Poéticas nacionalistas na música brasileira de concerto : proposições de Camargo Guarnieri e Cláudio Santoro - Vieira, Adinil Carlos da Silva (2017)
From the examination of historical data, and paying attention to the different poetic lines of two composers who are part of the framework of Brazilian nationalist composers, Camargo Guarnieri and Cláudio Santoro, try this research highlight the particularities and nuances of Brazilian nationalist music, so that refute the idea of a nationalism with a single and cohesive version. For this, studies on aesthetics, history, and mainly music were used. We also cite some of the major Brazilian composers who were in evidence in the first half of the twentieth century, as well as musical critics, punctuating questions about nationalist ideology in concert music. Considering the trajectories of Cláudio Santoro and Guarnieri, especially the nationalist music developed by them, we found some proposals for development of a national music, and we pay attention to the outcomes of the same. The particularities of these proposals as well as their outcome is thus the focus of this research. Taking into account two works for solo piano, Dansa Negra (Guarnieri) and Dansa Brasileira nº 02 (Santoro), this research found that the endings of the stylistic paths of both Guarnieri and Santoro gradually distance themselves from the main objective of nationalism, that is , to make the composers speak the national musical language as their mother tongue, to reflect the aspirations of a people, and to be assimilated by it.